Treatment With the Delta Opioid Agonist UFP-512 Alleviates Chronic Inflammatory and Neuropathic Pain: Mechanisms Implicated - Polo, Sara; Díaz, Andrés Felipe; Gallardo, Núria; Leánez, Sergi; Balboni, Gianfranco; Pol, Olga (Frontiers in Pharmacology, 2019)
We investigated whether administration of the δ-opioid receptor (DOR) agonist H-Dmt-Tic-NH-CH(CH2-COOH)-Bid (UFP-512), which also activates nuclear factor erythroid 2-related factor 2 (Nrf2), alleviated chronic inflammatory and/or neuropathic pain and inhibited the depressive-like behaviors associated with persistent neuropathic pain. The possible mechanisms implicated were also assessed. We evaluated the following effects in male C57BL/6J mice with inflammatory pain induced by complete Freund’s adjuvant or neuropathic pain caused by the chronic constriction of sciatic nerve: (1) the antinociceptive effects of UFP-512; (2) the effects of UFP-512 on the expression of Nrf2, heme oxygenase 1 (HO-1), NAD(P)H quinone oxidoreductase 1, phosphoinositide 3-kinase (PI3K), protein kinase B (Akt), inducible nitric oxide synthase, DOR, and mitogen-activated protein kinases (MAPK) in the spinal cord of animals with inflammatory or neuropathic pain; (3) the antinociceptive effects of the coadministration of UFP-512 with the Nrf2 activator sulforaphane (SFN); and (4) the antidepressant effects of UFP-512 in animals with depressive-like behaviors associated with neuropathic pain. Our results demonstrated that the intraperitoneal administration of UFP-512 inhibited chronic inflammatory and neuropathic pain and reduced the depressive-like behaviors associated with persistent neuropathic pain. The antiallodynic effects of UFP-512 were significantly augmented when it was coadministered with SFN in both types of chronic pain. The administration of UFP-512 increased/reestablished the spinal cord protein levels of Nrf2 and HO-1 in mice with inflammatory or neuropathic pain. However, while during inflammatory pain UFP-512 inhibited spinal c-Jun N-terminal kinase (JNK) and extracellular signal regulated kinase 1/2 (ERK1/2) phosphorylation induced by peripheral inflammation. This DOR agonist blocked the spinal activated PI3K/Akt signaling pathway under chronic neuropathic pain conditions, but it did not alter the enhanced protein levels of p-JNK or p-ERK1/2 induced by sciatic nerve injury. These results revealed the antinociceptive and antidepressant effects of UFP-512 in animals with chronic pain and the different mechanism of action of this DOR agonist in the presence of inflammatory or neuropathic pain. Our data also suggest the administration of UFP-512 as an alternative for the treatment of chronic pain and the depressive-like behaviors associated with neuropathic pain.